Environmental Justice: Linking Human Rights and the Environment - De Silva, S.S.M. (My University, 2008)
This study outlines the international legal regime on environmental protection and then examines the link between the environment and human rights by reference to the applicaion of human rights law as a legal remedy for environmental issue. Several decades ago, Public International Law not concerned with environmental protecion. The Stockholm conference of 1972 and subsequent international instruments have enriched the international community on the subject. Undoubtedly environmental rights are self executing and they need positive State intervention for their fulfillment. The human fights both procedural and substantive human rights, found in the international Bill of Rights are being applied in relation to environmental issues. The procedural rights must be distinguished from substantive rights recognized in international human rights instruments such as the right to life, the right to health or the right to decent standard of living. The invocatin of substantive human rights in relation to environmental issues has become popular at the national level. The efforts made by Sri Lanka and several South Asian countries are of considerable value. The right to a healthy environment on the other hand denotes the identification of a separate indepedent human right not dependent on existing human rights in the incorporation of a human right to healthy environment into the fundamental rights chapter of our Constitution.